A Study of the Relationship Between CMV IgG Titers and Blood Pressure in Iraqi patients - Mohammed , Maryam Kamel (Iraqi Journal of Science, 2023)
Human cytomegalovirus (CMV) infection is associated with higher risk of cardiovascular diseases in immunocompromised organ transplant patients; it has been linked with the elevated arterial blood pressure. This study aimed to find a relationship between CMV antibody titers and blood pressure elevation by using the enzyme-linked immunosorbent assay (ELISA) to measure CMV IgG levels in the serum of 60 patients with high blood pressure, in comparison to 30 healthy persons with normal blood pressure as a control. All patients and control were 25-50 years old. The results showed that CMV antibody titers were higher in those who undergo blood pressure elevation. This finding supports the hypothesis that; the common CMV infection may leads to impaired vascular function.